A MATLAB Toolbox for Findable, Accessible, Interoperable, and Reusable Atom Probe Data Science - Heller, Martina; Ott, Benedict; Dalbauer, Valentin; Felfer, Peter (Microscopy and Microanalysis, 2024)
Atom probe tomography (APT) data analytics have traditionally been based on manual analytics by researchers. As newer atom probes together with focused ion beam–based specimen preparation have opened APT to many more materials, yielding much more complex mass spectra, building up a systematic understanding of the pathway from raw data to final interpretation has increasingly become important. This demands a system in which the data and treatment can be traced, ideally by any interested party. Such an approach of findable, accessible, interoperable, and reusable (FAIR) data and analysis policies is becoming increasingly important, not just in APT. In this paper, we present a toolbox, written in MATLAB, which allows the user to store the raw and processed data in a standardized FAIR format (hierarchical data format 5) and process the data in a largely scriptable environment to minimize manual user input. This allows for the experiment data to be interchanged without owner explanations and the analysis to be reproduced. We have devised a metadata scheme that is extensible to other experiments in the materials science domain. With this toolbox, collective knowledge can be built up, and a large number of data sets can be analyzed in a fully automated fashion.
CRIS-Team Scopus Importer:2025-04-01
Keywords: atom probe data base; FAIR atom probe data science; HDF5; storage of APT data

Analyzing the Precipitation Effects in Low-Alloyed Copper Alloys Containing Hafnium and Chromium - Dölling, Julia; Kuglstatter, Moritz; Prahl, Ulrich; Höppel, Heinz Werner; Ortner, Patrick; Ott, Benedict; Kracun, Stefanie Felicia; Fehlbier, Martin; Zilly, Andreas (Metals, 2024)
Copper alloys containing chromium and hafnium combine elevated mechanical strength and high electrical and thermal conductivity. For the simultaneous enhancement of both material properties, precipitation hardening is the utilized mechanism. Therefore, the aim is to analyze the influence of chromium and hafnium in binary and ternary low-alloyed copper alloys and to compare the precipitation processes during temperature exposure. Atom probe tomography (APT) and differential scanning calorimetry (DSC) measurements enable to understand the precipitation sequence in detail. CuCr0.7 starts to precipitate directly, whereas CuHf0.7 is highly influenced by prior diffusion facilitating cold rolling. Within the ternary alloy, hafnium atoms accumulate at the shell of mainly Cr-containing precipitates. Increasing the local hafnium concentration results in the formation of intermetallic CuHf precipitates at the sites of mainly Cr-containing precipitates. Indirect methods are utilized to investigate the materials’ properties and show the impact of cold rolling prior to an aging treatment on binary alloys CuCr and CuHf. Finally, ternary alloys combine the benefits of facilitated precipitation processes and decelerated growing and coarsening, which classifies the alloys to be applicable for usage at elevated temperatures.<br
Keywords: copper–hafnium CuHf; copper–chromium CuCr; CuHfCr; atom probe tomography APT; differential scanning calorimetry DSC; precipitation hardening; precipitation mechanism; cold working; cold rolling; conductivity improvement; high-performance copper alloy; conduction materials; electrical and automotive engineering

Analyzing the Precipitation Effects in Low-Alloyed Copper Alloys Containing Hafnium and Chromium - Dölling, Julia; Kuglstatter, Moritz; Prahl, Ulrich; Höppel, Heinz Werner; Ortner, Patrick; Ott, Benedict; Kracun, Stefanie Felicia; Fehlbier, Martin; Zilly, Andreas (Metals, 2024)
Copper alloys containing chromium and hafnium combine elevated mechanical strength and high electrical and thermal conductivity. For the simultaneous enhancement of both material properties, precipitation hardening is the utilized mechanism. Therefore, the aim is to analyze the influence of chromium and hafnium in binary and ternary low-alloyed copper alloys and to compare the precipitation processes during temperature exposure. Atom probe tomography (APT) and differential scanning calorimetry (DSC) measurements enable to understand the precipitation sequence in detail. CuCr0.7 starts to precipitate directly, whereas CuHf0.7 is highly influenced by prior diffusion facilitating cold rolling. Within the ternary alloy, hafnium atoms accumulate at the shell of mainly Cr-containing precipitates. Increasing the local hafnium concentration results in the formation of intermetallic CuHf precipitates at the sites of mainly Cr-containing precipitates. Indirect methods are utilized to investigate the materials’ properties and show the impact of cold rolling prior to an aging treatment on binary alloys CuCr and CuHf. Finally, ternary alloys combine the benefits of facilitated precipitation processes and decelerated growing and coarsening, which classifies the alloys to be applicable for usage at elevated temperatures.
CRIS-Team Scopus Importer:2024-04-05
Keywords: atom probe tomography APT; cold rolling; cold working; conduction materials; conductivity improvement; copper–chromium CuCr; copper–hafnium CuHf; CuHfCr; differential scanning calorimetry DSC; electrical and automotive engineering; high-performance copper alloy; precipitation hardening; precipitation mechanism

An Atom Probe with Ultra-Low Hydrogen Background - Felfer, Peter; Ott, Benedict; Monajem, Mehrpad; Dalbauer, Valentin; Heller, Martina; Josten, Jan; Macaulay, Chandra (Microscopy and Microanalysis, 2021)
Atom probe tomography (APT) is a single-ion sensitive time-of-flight mass spectrometry method with near-atomic spatial resolution. In principle, it can be used to detect any chemical element, but so far hydrogen in the form of protium (H-1) had to be largely excluded. This is owing to the residual H emitted from the stainless-steel chambers and in-vacuum parts commonly used in atom probe instrumentation. This residual H is then picked up in the APT experiment. In this paper, we show that by replacing the stainless-steel chamber and in-vacuum parts with titanium parts, this residual H can largely be removed, thus enabling the direct imaging of H using APT. We show that besides the drastic reduction of H, also other contaminants such as O, OH, and H2O are reduced by employing this instrument. In the current set-up, the instrument is equipped with high-voltage pulsing limiting the application to conductive materials.
CRIS-Team WoS Importer:2021-12-31

Compensating Image Distortions in a Commercial Reflectron-Type Atom Probe - Heller, Martina; Ott, Benedict; Felfer, Peter (Microscopy and Microanalysis, 2024)
In atom probe tomography, the spatial resolution and accuracy of the data critically depend on the 3D reconstruction of the 2D detector data. Atom probes with a reflectron have an improved mass resolving power and must include a model of the imaging properties of the reflectron. However, for modern wide-angle reflectron instruments, these imaging properties are not trivial and need to be determined for the reflectron used. This is typically done by the instrument manufacturer, and due to the proprietary nature of the instrument design, the imaging properties are opaque to the user. In this paper, we provide a method to determine the imaging properties of a reflectron that can easily be carried out on commercial instrumentation. This method is used to provide the user with a transformation function from the provided detector data, which can already contain some corrections applied, to a virtual detector placed before the reflectron. From there on, 3D reconstructions can be carried out analogous to straight flight path instruments. Correction algorithms and reference data for Imago/CAMECA LEAP 3000, 4000, 5000, and 6000 series instruments are also provided.
CRIS-Team Scopus Importer:2025-04-01
Keywords: APT data correction; atom probe; reflectron

Miniaturized gas exposure devices for atom probe experiments - Ott, Benedict; Heller, Martina; Monajem, Mehrpad; Felfer, Peter (Microscopy research and technique, 2024)
To detect hydrogen in materials at the atomic scale, atom probe tomography is now regularly used. In order to avoid cumbersome cryo-preparation to suppress diffusion, often hydrogen is charged only into the finished specimen. Here, the use of hydrogen gas over electrochemical hydrogen has the advantage that the specimen is not contaminated with an electrolyte. So far, this “charging” has been done in large, expensive systems. Here, we introduce small devices that enable the exposure of atom probe specimens to hydrogen and potentially other gases, using only very small gas volumes. This enables the operation in regular laboratory environments without additional safety measures. These devices can be used to expose the specimen to hydrogen up to 10 bar/90°C. Higher temperatures may be attained with small changes. Validation of the success of charging with these setups is demonstrated through experiments employing deuterium charging of palladium atom probe tips. Research Highlights: Enabling the exposure of atom probe specimens to hydrogen and potentially other gases, using only very small gas volumes. Built setups can be assembled with little money and from freely available parts, making specimen charging much easier. Validation of the success of charging with these setups is demonstrated through experiments employing deuterium charging of palladium atom probe tips.
CRIS-Team Scopus Importer:2024-05-10
Keywords: atom probe; atom probe tomography; deuterium; deuterium gas charging

Role of Si segregation in the structural, mechanical, and compositional evolution of high-temperature oxidation resistant Cr-Si-B2±z thin films - Zauner, L.; Steiner, A.; Glechner, T.; Bahr, A.; Ott, Benedict; Hahn, R.; Wojcik, T.; Hunold, O.; Ramm, J.; Kolozsvári, S.; Polcik, P.; Felfer, Peter; et al. (Journal of Alloys and Compounds, 2023)
This work investigates the influence of Si-alloying up to 17 at.% on the structural, mechanical, and oxidation properties of magnetron sputtered CrB2±z-based thin films. Density-functional theory calculations combined with atom probe tomography reveal the preferred Si occupation of Cr-lattice sites and an effective solubility limit between 3 to 4 at.% in AlB2-structured solid solutions. The addition of Si results in refinement of the columnar morphology, accompanied by enhanced segregation of excess Si along grain boundaries. The microstructural separation leads to a decrease in both film hardness and Young's modulus from H ∼ 24 to 17 GPa and E ∼ 300 to 240 GPa, respectively, dominated by the inferior mechanical properties of the intergranular Si-rich regions. Dynamic thermogravimetry up to 1400 °C reveals a significant increase in oxidation onset temperature from 600 to 1100 °C above a Si content of 8 at.%. In-situ X-ray diffraction correlates the protective mechanism with thermally activated precipitation of Si from the Cr-Si-B2±z solid solution at 600 °C, enabling the formation of a stable, nanometer-sized SiO2-based scale. Moreover, high-resolution TEM analysis exposes the scale architecture after dynamic oxidation to 1200 °C (10 K/min heating rate) – consisting only of ∼20 nm amorphous SiO2 beneath ∼200 nm of nanocrystalline Cr2O3. In summary, the study provides detailed guidelines connecting the chemical composition with the respective thin film properties of high-temperature oxidation resistant Cr-Si-B2±z coatings.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Borides; Mechanical properties; Oxidation resistance; Phase stability; Segregation; Si alloying; Thin films

Specimen preparation for atom probe tomography - Felfer, Peter; Ott, Benedict; Vorlaufer, Nora (Praktische Metallographie, 2024)
In the past 20 years or so, atom probe tomography has gone from a niche technique in physical metallurgy to a well-established method in many parts of materials science and beyond. This is owing to the improvement in both instrumentation and specimen preparation. Given the availability of instruments, successful specimen preparation is often the bottleneck in atom probe projects. In this article, the authors want to give an overview of the types of preparation techniques that are available and which challenges they pose. This includes basic electropolishing, which was dominant until the introduction of focused ion beam-based preparation some 25 years ago. Nowadays, focused ion beam-based preparation methods possibly represent the largest share, as they allow for site-specific specimen preparation, non-conductive specimens and often a higher throughput. They are continuously improved, i. e., through higher current plasma ion columns, cryo preparation for sensitive materials and room temperature liquids and 'additive' techniques for nanomaterials. This steadily increases the types of materials that can be analyzed using atom probe tomography.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Atom probe tomography; electropolishing; nanomaterials; preparation